THE PERFORMANCE OF THE YOGYAKARTA CITY GENERAL ELECTION COMMISSION IN FACILITATING PERSONS WITH DISABILITIES DURING THE 2024 GENERAL ELECTION VOTING PROCESS - Deren Wahyu Prasetia; Pangky Febriantanto (PT. Radja Intercontinental Publishing, 2026)
The 2024 general election was an important moment for assessing the extent to which the Yogyakarta City General Election Commission (KPU) facilitated persons with disabilities during the voting process. Although the KPU had established inclusive policies to support the participation of voters with disabilities, several challenges remained in implementation. The main issues were limited accessibility, uneven dissemination of information, and infrastructure constraints influenced by the geographic and social conditions of Yogyakarta City. The findings show that efforts to improve accessibility for persons with disabilities have been carried out, but obstacles are still found in the transparency and accountability of information regarding voting rights and available facilities. The effectiveness and efficiency of implementation also need to be strengthened so that election services can respond more appropriately to the needs of voters with disabilities. Community participation was pursued through socialization programs and the involvement of disability communities. These findings provide recommendations for improving policies and election implementation so that future elections become more responsive, inclusive, and accessible to all citizens.